LIGNIN AND CARBON ISOTOPES COMPOSITION OF SUSPENDED PARTICULATES BY CAPILLARY GAS CHROMATOGRAPHY OF CUPRIC OXIDE OXIDATION PRODUCTS - Waode Rustiah; Alfian Noor; Maming Maming; Muhammad Lukman (Hasanuddin University, 2018)
Lignin are high molecular weight phenolic polymers that occur as major constituents of vascular plants. As a result of their natural abundance, wide distribution, and resistance to microbial degradation, lignin are also commonly found in soil and sedimentary organic matter. The aim of this study was to identify the contribution of lignin to the suspended particulate fraction in the Losari Beach and Lae-lae Island, where indicate highly degraded lignin materials. Lignin was characterized by oxidative degradation, cupric oxide being chosen as the most suitable oxydizing agent to produce simple lignin-derived phenols that are extracted with hexane and analyzed by capillary gas chromatography on fused silica columns, provides the high sensitivity and precision required for the identification and quantitation of trace levels of lignin in seawater. A suite of up to 8 phenols is produced that reflects the relative concentration and plant tissue sources of lignin present in the suspended material.